7P Marketing Mix Strategy at Batoe 54 Swimming Pool, Jakarta - Fitria, Putri Maulida; Nugraha, Rizki Nurul; Bule, Yohana Gaius (Westscience Press, 2024)
The study was conducted at Batoe 54 Swimming Pool located in Jl.HM Nalim Jagakarsa, South Jakarta. The formulation of this research problem is what is the tourist attraction in the Batoe 54 swimming pool, how to implement the 7P marketing mix strategy in the Batoe 54 Swimming Pool, and why a marketing mix strategy is needed in these destinations. The purpose of the study was to find out the tourist attraction offered by the Batoe 54 swimming pool, find out more about the 7P marketing mix strategy implemented by the Batoe 54 swimming pool, and provide insight into how artificial tourist destinations can increase their competitiveness in an increasingly competitive tourism market. Data collection was carried out by direct observation and interviews with destination managers and several visitors. The research method uses qualitative, with a qualitative descriptive approach. The results showed that Batoe 54 Swimming Pool is suitable for lower middle class visitors because the prices offered are cheap, the facilities provided are complete, employee service is good, and the location is strategic. Batoe 54 Swimming Pool has shortcomings such as moss in the pool, lack of promotion, and some facilities are still not suitable for use. Strategies to overcome these shortcomings are improving product quality, adjusting prices more competitively, more effective promotions, paying attention to customer service aspects, and the physical environment so that the visitor experience becomes better.